Stakeholder participation in building resilience to disasters in a changing climate. (2nd January 2016) - Aldunce, Paulina; Beilin, Ruth; Handmer, John; Howden, Mark
ABSTRACT: The resilience perspective has emerged as a plausible approach to confront the increasingly devastating impacts of disasters; and the challenges and uncertainty climate change poses through an expected rise in frequency and magnitude of hazards. Stakeholder participation is posited as pivotal for building resilience, and resilience is not passive; rather, stakeholders are actively involved in the process of building resilience. Who is involved and how they are involved are crucial aspects for developing resilience in practice. Nevertheless, there are few empirical studies available to inform theory or show how these issues are addressed. This study focuses on revealing how practitioners frame the issue of participation in relation to resilience, its relevance to a changing climate and how, in consequence, they construct practices. Using Hajer's [(1995). The politics of environmental discourse: Ecological modernization and the policy process . New York] 'Social-interactive discourse theory', in this interdisciplinary research, we study the frames and subsequent practices developed around a disaster management policy initiative in Australia: the Natural Disaster Resilience Program in Queensland. What emerges from the research findings as critical and requiring urgent attention is stakeholder and especially local government and community participation, and for this to become socially relevant, challenges such as meaningful communication and power structures need to be addressed. What is also critical is to move from experiential learning to social learning. Additionally, the results presented here offer empirical evidence on how broadening the pool of actors can be implemented, and the opportunities that this opens up for building resilience.